Bioaktivitas Produk Fermentasi Monascus - Srianta, Ignatius; Widharna, Ratna Megawati; Kardono, Leonardus Broto S. (Jurnal Farmasi Sains dan Terapan, 2013)
Monascus-fermented product has been used traditionally in Asian countries as food and medicine. Traditionally, Monascus-fermented rice was produced with cultivate Monascus sp. on steamed rice medium. During fermentation, Monascus sp. produce various metabolites. Beside pigments, Monascus sp. also produces monacolin K, monascin, dimerumic acid, etc which possess positive health impacts. Recent studies reported that Monascus sp. could grow on non rice medium i.e. soybean, dioscorea, adlay etc. This paper is a review of bioactivities of Monascus-fermented products including anti-inflammatory, anti hypercholesterolemic, anti hyperlipidemia, anti hypertensive, antioxidant and anti diabetes activities.